The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/star.200500468
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cross‐linking with Epichlorohydrin on the Properties of Cassava (Manihot esculenta Crantz) Starch

Abstract: Cassava starch was cross‐linked with epichlorohydrin (EPI) at 45°C for 2 h in three different media which include water, water in the presence of a phase transfer catalyst (PTC) and N,N‐dimethylformamide (DMF). The products were characterized by determining their physicochemical, thermal and retrogradation properties. In aqueous medium, the use of a PTC, tetrabutylammonium bromide (TBAB) produced derivatives with higher degree of cross‐linking than those prepared without the use of the catalyst. The degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
137
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(154 citation statements)
references
References 19 publications
10
137
0
Order By: Relevance
“…The results were consistent with those of cross-linked cassava starch (Jyothi et al, 2006), waxy maize starch (Hirsch and Kokini, 2002), and taro starch (Hazarika and Sit, 2016).…”
Section: Swelling Factorsupporting
confidence: 87%
“…The results were consistent with those of cross-linked cassava starch (Jyothi et al, 2006), waxy maize starch (Hirsch and Kokini, 2002), and taro starch (Hazarika and Sit, 2016).…”
Section: Swelling Factorsupporting
confidence: 87%
“…The degree of cross-linking of the modified starches was determined from the RVA viscosity values are also presented in Table 1. It was observed that at lower level of EPI (0.3%), the degree of cross-linking of rice and maize starch was not detectable by the viscosity method, the degree of cross-linking of theses starches was not great enough to restrict the swelling of the granules and these exhibited higher peak viscosity values than that of the native starch (Jyothi et al, 2006). However the degree of cross-linking of cross-linked and oxidized cross-linked potato starch was detectable (60.1 and 20.0, respectively), higher level of cross-link of potato starch retarded the swelling of granules, resulting in a lower peak viscosity.…”
Section: Degree Of Cross-linking and Contents Of Carboxyl And Carbonymentioning
confidence: 98%
“…Singh et al (2007) observed decrease in retrogradation rate and increase in gelatinization temperature with cross-linked starch, and these phenomena are related to the reduced mobility of amorphous chains in the starch granule as a result of intermolecular bridges. However, Jyothi et al (2006) showed that cross-linked starch has more pronounced synaeresis than native starch because of ordered structure in the starch paste, thus resulting in a higher degree of retrogradation.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the reagent used for crosslinking, the final product is classified in one of three types: i) monostarch phosphate produced by starch esterification with orthophosphoric acid, potassium or sodium orthophosphoric or STPP; ii) distarch phosphate produced when native starch reacts with STMP or PDCl 3 ; or iii) phosphated distarch phosphate, resulting from combined treatments of monostarch and distarch phosphates (Gunaratne & Corke, 2007;Jyothi et al, 2006).…”
Section: Cross-linked Starchmentioning
confidence: 99%